PENINGKATAN PENDAPATAN IBU PKK DENGAN MENERAPKAN VERTICAL GARDEN MENGGUNAKAN BOTOL BEKAS PADA MASA PANDEMI COVID-19 DI KELURAHAN LUBUK PAKAM PEKAN KECAMATAN LUBUK PAKAM - Adelina Lubis Lubis (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2022)
The Covid-19 pandemic has caused social and economic changes in society, As a result of this situation, many workers were laid off and there were layoffs which resulted in unemployment. Agriculture is one sector that has high resilience in dealing with various economic problems. This service activity aims to foster and empower women housewives to grow crops using plastic bottle waste to increase family income. This service is carried out in Lubuk Pakan Pekan Village, Lubuk Pakam District. The selection of this location is based on data from the BPS Deli Serdang, that there are 264 residents of Lubuk Pakam District who generally do not have permanent jobs. The service partners in this PkM activity are a group of PKK women in Lubuk Pakam District totaling twenty women whose husbands are casual daily laborers. The method used in this PkM is counseling, namely socialization, training, and assistance to partners. The existence of this PKM activity is expected to be right on target, namely to increase partners' food security, a solution for partners who want to grow crops but do not have large areas of land and create a beautiful environment and increase family income.